PENYULUHAN TENTANG PENGGUNAAN EKSTRAK RIMPANG KUNYIT UNTUK PENGOBATAN DIARE DI PUSKESMAS TANJUNG MORAWA - Linta Meliala; Angga Nugraha Sanjaya (INSTITUT KESEHATAN DELI HUSADA, 2021)
The instructions on the utilization of turmeric rhizome extricate for the treatment of loose bowels at the Tanjung Morawa Wellbeing Center means to apply the data and improvements that have been acquired by understudies in more extensive conversations in the neighborhood. Looseness of the bowels or otherwise called gastroenteritis is one of the most well-known infections locally. The justification for holding this PKM is to get data about the utilization of turmeric separate for the treatment of the runs at the Tanjung Morawa Wellbeing Center. The runs is typically portrayed by the recurrence of defecations that surpass the ordinary recurrence, watery consistency, intense and persistent. Intense looseness of the bowels is portrayed by diseases brought about by Escherichia coli, Shigella sp, Salmonella sp, infections, amoebic microscopic organisms, and can likewise be brought about by bacterial poisons, for example, Staphylococcus aureus, Clostridium welchii that sully food, while constant the runs is related with gastrointestinal problems. . Turmeric rhizome is a plant that can be utilized as conventional medication. One sort of plant that can be utilized for the treatment of diarrheal infection is turmeric (Curcuma domestica Val.)